Anti-Collition Device (ACD) Lokomotif Diesel Electric Seri CC201 Dengan Induksi Dual Tone Multiple Frequency (DTMF) - Darmawan, Arief; Winjaya, Fathurozzi (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2018)
Railroad transportation has characteristics in the pattern of operation that a block block is only allowed to be passed by a train facility whose safety is guaranteed by the railroad signaling system. The existing signaling system in Indonesia currently uses a wayide signal aspect indicator and has not been equipped with a warning and protection system against violations of the unsafe signal aspect / SPAD (Signal Pass At Danger) or speed limit violations. To improve travel safety absolutely requires warning equipment for drivers about violations of signal aspects and violations of speed restrictions. This study discusses the calculation of the braking profile on the CC201 series electric locomotive and the Anti-Collition Device (ACD) prototype design using the Audio Frequency (AF) induction system using Dual Tone Multiple Frequency (DTMF) coding as well as the Atmel AT89S52 type Microcontroller control system. Based on the analysis of the braking distance at a speed of 120 Km / h using the minden method, the AF sensor is installed at a distance of 1,168.79 meters before the incoming signal. Based on the measurement results of the signal intensity received by the DTMF locomotive sensor, the biggest signal is at the gap gap between the AF sensors with a distance of 80 mm, while for the lowest reading level at a distance of 120mm.